ANALISIS USABILITY WEBSITE BOARDIFY SEBAGAI PLATFORM KOLABORASI PENELITIAN MAHASISWA : ANALYSIS OF THE WEBSITE USABILITY OF BOARDIFY AS A STUDENT RESEARCH COLLABORATIVE PLATFORM - Wirda Syahrifa; Muhammad Fikry; Zara Yunizar (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
This study aims to analyze the usability level of the Boardify website as a student research collaboration platform. This study uses the A/B Testing method by comparing the Boardify and Trello platforms. A total of 55 respondents participated in each platform and were asked to fill out a questionnaire consisting of 25 identical questions. Additionally, technical performance testing of the Boardify website was conducted using the GTmetrix tool. The results of the study indicate that Boardify achieved an average usability score of 99.18, indicating that the platform is highly user-friendly and aligns with user needs in the context of final project submissions. In terms of performance, GTmetrix test results showed that Boardify received a Grade B with a Performance score of 86% and a Structure score of 90%. The use of A/B Testing provided an objective overview of the user experience when compared to similar platforms. Thus, Boardify can be deemed suitable and effective for use as a collaboration platform in student research.